2021
DOI: 10.1021/acs.joc.1c00439
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Studies of Stable Nonaromatic Dithia Pyribenzihexaphyrins

Abstract: We report here one of the rare examples of expanded hexaphyrins named as dithia pyribenzihexaphyrin macrocycles containing six-membered rings such as pyridine and p-phenylene along with five-membered heterocycles such as pyrrole and thiophene as a part of a macrocyclic frame. Trifluoroacetic acid catalyzed [3 + 3] condensation of equimolar mixture of [10,10′bis(p-tert-butyl phenyl)hydroxymethyl]-1,3-bis(2-thienyl)pyridine diol (2,6-pyri diol) and 1,4-bis(phenyl(1H-pyrrol-2-yl)methyl)benzene (p-benzidipyrrane) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Interestingly, the lower energy band maxima of compounds 4 – 6 and their protonated forms 4.2H + – 6.2H + was blue shifted compared to our previously reported macrocycles 1 and 2 . This was attributed to the disruption in the π‐conjugation in the macrocycles 4 – 6 and enhanced flexibility due to incorporation of polyether linkage into the macrocyclic framework [24,25] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the lower energy band maxima of compounds 4 – 6 and their protonated forms 4.2H + – 6.2H + was blue shifted compared to our previously reported macrocycles 1 and 2 . This was attributed to the disruption in the π‐conjugation in the macrocycles 4 – 6 and enhanced flexibility due to incorporation of polyether linkage into the macrocyclic framework [24,25] …”
Section: Resultsmentioning
confidence: 99%
“…This was attributed to the disruption in the π-conjugation in the macrocycles 4-6 and enhanced flexibility due to incorporation of polyether linkage into the macrocyclic framework. [24,25] The redox properties of pyridine containing crowned expanded porphyrins 4-6 were investigated using cyclic voltammetry and differential pulse voltammetry in CH 2 Cl 2 and the relevant data are included in Table 1. The cyclic voltammograms along with differential pulse voltammograms of compounds 4-6 presented in Figure 4c showed that the compounds 4-6 in general showed three reversible/quasi-reversible oxidations and one irreversible reduction.…”
Section: Absorption and Electrochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first attempt to synthesize pyriporphyrin was done by Berlin and Breitmaier through [3 + 1] MacDonald type condensation between pyridine-2,6-dicarbaldehyde with tripyrran to obtain pyriporphyrinone instead of pyriporphyrin . Thereafter, a plethora of pyridyl derivatives are reported which encompassed, true pyriporphyrin, confused pyriporphyrin, expanded pyriporphyrin, and its coordination complexes. , …”
Section: Pyriporphyrinoidsmentioning
confidence: 99%